2013
DOI: 10.1007/s12328-013-0434-6
|View full text |Cite
|
Sign up to set email alerts
|

Unruptured cystic artery pseudoaneurysm accompanied by Mirizzi syndrome: a report of a case

Abstract: Pseudoaneurysm of the cystic artery is a rare complication of cholecystitis. 34 cases have been reported from 1976 to 2012, searched on MEDLINE and most of the cases have presented with gastrointestinal bleeding. We report the third case of an unruptured pseudoaneurysm of the cystic artery associated with calculous cholecystitis. An 85-year-old female presented to the emergency unit with epigastric pain and jaundice. Laboratory data and contrast-enhanced computed tomography (CT) revealed calculous cholecystiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The curative treatment for cholecystitis and Mirizzi syndrome complicated by hemobilia and hepatic aneurysm, such as in this case, is basically cholecystectomy because of the possibility of recurrent hemorrhage and carcinoma development [ 11 14 ]. It has recently been reported that TAE is minimally invasive, can be performed following angiographic diagnosis, and that control of bleeding by TAE is accomplished prior to radical surgery [ 15 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The curative treatment for cholecystitis and Mirizzi syndrome complicated by hemobilia and hepatic aneurysm, such as in this case, is basically cholecystectomy because of the possibility of recurrent hemorrhage and carcinoma development [ 11 14 ]. It has recently been reported that TAE is minimally invasive, can be performed following angiographic diagnosis, and that control of bleeding by TAE is accomplished prior to radical surgery [ 15 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, we considered the possibility of worsening of inflammation and necrosis of the gallbladder due to gallbladder infarction, rebleeding due to persistent inflammation, and severe cholangitis due to hematoma in the bile duct; consequently, we performed emergency surgery on the same day. Although surgery is the first choice for Mirizzi syndrome, TAE has been reported to be effective for aneurysms associated with hemobilia [ 15 17 ]. And in this case, we performed cholecystectomy after TAE.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging in the form of ultrasound with colour doppler, CT angiography or dynamic magnetic resonance imaging can be used to make the diagnosis. Selective hepatic arterial angiography provides both a diagnostic and therapeutic option 1,3 . This is the preferred method of treatment prior to an operation to avoid bleeding during cholecystectomy 3 …”
Section: Figurementioning
confidence: 99%
“…Selective hepatic arterial angiography provides both a diagnostic and therapeutic option. 1,3 This is the preferred method of treatment prior to an operation to avoid bleeding during cholecystectomy. 3 To the authors' knowledge, this is the first case described in the literature of Mirizzi syndrome and right hepatic artery pseudoaneurysm with concurrent cholecystoduodenal fistula.…”
mentioning
confidence: 99%
See 1 more Smart Citation